Calcium Hydride Cation Dimer Catalyzed Hydrogenation of Unactivated 1‐Alkenes and H2 Isotope Exchange: Competitive Ca−H−Ca Bridges and Terminal Ca−H Bonds - Qu, Zheng‐Wang; Zhu, Hui; Grimme, Stefan (Chemistry : a European journal, 2023)
Recently, it was shown that the double Ca−H−Ca bridged calcium hydride cation dimer complex [LCaH2CaL]2+ (macrocyclic ligand L=NNNN‐tetradentate Me4TACD) exhibited remarkable activity in catalyzing the hydrogenation of unactivated 1‐alkenes as well as the H2 isotope exchange under mild conditions, tentatively via the terminal Ca−H bond of cation monomer LCaH+. In this DFT mechanistic work, a novel substrate‐dependent catalytic mechanism is disclosed involving cooperative Ca−H−Ca bridges for H2 isotope exchange, competitive Ca−H−Ca bridges and terminal Ca−H bonds for anti‐Markovnikov addition of unactivated 1‐alkenes, and terminal Ca−H bonds for Markovnikov addition of conjugation‐activated styrene. THF‐coordination plays a key role in favoring the anti‐Markovnikov addition while strong cation‐π interactions direct the Markovnikov addition to terminal Ca−H bonds. Calcium hydride cation dimer catalysis: Dispersion‐corrected DFT calculations reveal that the same double Ca−H−Ca bridged calcium hydride cation dimer catalyst [LCaH2CaL]2+⋅THF shows a novel substrate‐dependent catalytic activity, involving cooperative Ca−H−Ca bridges for efficient H2 isotope exchange, terminal Ca−H bond for the Markovnikov addition of conjugation‐activated styrene, and competitive Ca−H−Ca bridges and terminal Ca−H bonds for the anti‐Markovnikov addition of unactivated 1‐alkenes.